Barriers to the Integration of Care in Inter-Organisational Settings: A Literature Review - Auschra, Carolin (Int J Integr Care, 2018)
INTRODUCTION: In recent years, inter-organisational collaboration between healthcare organisations has become of increasingly vital importance in order to improve the integration of health service delivery. However, different barriers reported in academic literature seem to hinder the formation and development of such collaboration. THEORY AND METHODS: This systematic literature review of forty studies summarises and categorises the barriers to integrated care in inter-organisational settings as reported in previous studies. It analyses how these barriers operate. RESULTS: Within these studies, twenty types of barriers have been identified and then categorised in six groups (barriers related to administration and regulation, barriers related to funding, barriers related to the inter-organisational domain, barriers related to the organisational domain, barriers related to service delivery, and barriers related to clinical practices). Not all of these barriers emerge passively, some are set up intentionally. They are not only context-specific, but are also often related and influence each other. DISCUSSION AND CONCLUSION: The compilation of these results allows for a better understanding of the characteristics and reasons for the occurrence of barriers that impede collaboration aiming for the integration of care, not only for researchers but also for practitioners. It can help to explain and counteract the slow progress and limited efficiency and effectiveness of some of the inter-organisational collaboration in healthcare settings.